The Effect of Dispositional Gratitude On Quality of Life In Fatherless Students - Salman Syafiq; Lila Pratiwi (Da'wa Faculty of Islamic State University Salatiga, 2025)
Fatherless college students often experience various psychological and social challenges due to the absence of a father role, both physically and functionally, which can affect their quality of life. Although several studies have shown a positive relationship between dispositional gratitude and quality of life in the general population, very few studies have specifically explored its role in vulnerable groups such as fatherless college students, especially in the Indonesian cultural context. This study aims to fill that gap by evaluating the influence of dispositional gratitude on quality of life in 129 fatherless university students in Jakarta through a quantitative approach and valid and reliable instruments, namely the Gratitude Questionnaire-Six (GQ-6) and the Indonesian Quality of Life Scale. The results of the simple linear regression analysis showed a positive and significant effect of gratitude on quality of life (R² = 0.096; p < 0.001), indicating that gratitude contributed 9.6% to the variation in quality of life. This finding suggests that dispositional gratitude is a psychological resource that has the potential to serve as an adaptive strategy for fatherless students in navigating the developmental pressures of early adulthood. Although its contribution is not dominant, this result opens up opportunities for further exploration of other variables, such as social support, resilience, spirituality, and life expectancy, to develop more targeted, holistic interventions that support the well-being of fatherless college students in Indonesia.